AN EVALUATION OF SELECTED MOROCCAN ELT TEXTBOOKS: A STANDARDS-BASED APPROACH PERSPECTIVE - Bouzid, Hassan Ait (Indonesian Journal of Applied Linguistics, 2017)
Standards-Based Approach to textbook evaluation has been blooming in recent decades. Nevertheless, this practice has received very little attention in Morocco.Â  The present study aims to bridge a gap in the literature of the Moroccan context by investigating the extent to which three locally designed ELT textbooks conform to the theoretical principles of the Standards-Based Approach which defines the teaching of English as a foreign language in the country (Ministry of National Education, 2007). Its objective is to examine whether and how these textbooks present contents that enable learners to meet the content standards included in the goal areas of Communications, Cultures, Connections and Comparisons. The study is informed by the theoretical framework of the Standards-Based Approach. It adopts a mixed-methods design that uses content analysis as a mixed data analysis method combining both quantitative and qualitative techniques. The findings reveal a number of shortcomings relevant to the representation of the content standards as several standards are not sufficiently addressed in the activities included in these textbooks. Eventually, some suggestions are addressed to policy makers, textbook designers and teachers to overcome the identified problems in current and future textbooks. The study is expected to sensitize ELT practitioners about the viability of using textbook evaluation in boosting both the quality of ELT textbooks and the quality of the teaching learning outcomes.